Genetic Variants of MSX1, PAX9, and AXIN2 in Mayan Probands with Dental Agenesis from Yucatan, Mexico - González-Pérez, Nayelli A. (2024)
The present study aimed to determine the genetic variants of PAX9, MSX1, and AXIN2 in Mayan probands with non-syndromic dental agenesis (NSDA) from Yucatan, Mexico. We sequenced DNA of specific exons of the PAX9, MSX1, and AXIN2 genes by using the Sanger method in seven Mayan probands with familial NSDA attending orthodontic clinics in Merida, Yucatan, Mexico. We bioinformatically analyzed four genomes of unaffected people with Mayan ancestry for comparative purposes. Two Mayan probands had oligodontia (14 or 16 missing teeth) and five had hypodontia (1-2 missing teeth). We found the following genetic variants: rs8670 in MSX1; rs12881240 and rs4904210 in PAX9; and rs1060502133, rs1060502139, rs147716924, rs1330822418, rs769741903, rs9915936, rs1133683, and rs1234437759 in AXIN2. The genetic variants in PAX9, MSX1, and AXIN2 in Mayan probands with familial NSDA were benign and have previously been reported. In conclusion, the AXIN2 gene exhibited the highest number of known variants. Because some variants were also present in the genomes of unaffected people, additional functional and epidemiological studies are required to address their clinical significance and associated phenotypes.